1991
DOI: 10.1002/j.1460-2075.1991.tb04916.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of the dsRNA unwinding/modifying activity.

Abstract: Double‐stranded RNA (dsRNA) unwinding/modifying activity, which is present in a wide range of eukaryotic cells, has been previously shown to convert up to 50% of adenosine residues to inosines within intermolecular dsRNA. In the present study, we report that this activity also modifies, though slightly less efficiently, intramolecular double‐stranded regions of synthetic RNAs. Our results widen the range of the possible biological substrates for the activity since many stem and loop type RNA secondary structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(151 citation statements)
references
References 34 publications
9
142
0
Order By: Relevance
“…Both intermolecular and intramolecular dsRNAs of >20 base pairs (bp) (two turns of the dsRNA helix) can serve as substrates for ADAR 47 . Many adenosine residues of a long, completely base-paired dsRNA (>100 bp) are edited non-selectively.…”
Section: Substrate and Editing-site Selectivitymentioning
confidence: 99%
“…Both intermolecular and intramolecular dsRNAs of >20 base pairs (bp) (two turns of the dsRNA helix) can serve as substrates for ADAR 47 . Many adenosine residues of a long, completely base-paired dsRNA (>100 bp) are edited non-selectively.…”
Section: Substrate and Editing-site Selectivitymentioning
confidence: 99%
“…Any double-stranded region of at least 15-20 base pairs may potentially be a substrate for ADARs (17). However, dsRNAs for ADARs can be broadly classified into nonspecific and specific types.…”
Section: Evolution Of Adar Targetsmentioning
confidence: 99%
“…While there is no discrete sequence motif common among substrates to direct the deamination of specific adenosine residues, distinct 5Ј-nearest neighbor sequence preferences have been identified for both ADAR1 (U ϭ A Ͼ C Ͼ G) and ADAR2 (U ϭ A Ͼ C ϭ G) using in vitro editing assays with artificial RNA duplexes and a 3Ј-nearest neighbor preference for ADAR2 has also been suggested (U ϭ G Ͼ C ϭ A) (7). While up to 50% of the adenosine residues within a perfect RNA duplex may be modified by ADAR1 and ADAR2 in vitro, RNA substrates whose duplex structures are interrupted by mismatches, bulges and loops are edited more selectively (20,21). Recent in vitro studies with synthetic RNA substrates have indicated that internal loops within ADAR substrates may serve to uncouple adjacent helices to convert long, promiscuously deaminated substrates into a series of short, selectively modified RNA targets (22).…”
mentioning
confidence: 99%